2008
DOI: 10.1002/jor.20668
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis of human articular chondrocytes and mesenchymal stem cells

Abstract: Migration of chondrocytes and mesenchymal stem cells (MSCs) may be important in cartilage development, tissue response to injury, and in tissue engineering. This study analyzed growth factors and cytokines for their ability to induce migration of human articular chondrocytes and bone marrow-derived mesenchymal stem cells in Boyden chamber assays. In human articular chondrocytes serum induced dose- and time-dependent increases in cell migration. Among a series of growth factors and cytokines tested only PDGF in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
124
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(137 citation statements)
references
References 33 publications
11
124
1
1
Order By: Relevance
“…PDGF has two receptor dimers, a and b. PDGF-AA binds a/a receptors, PDGF-AB binds a/a and a/b receptors, and PDGF-BB binds a/a, a/b, and b/b receptors. 46 In vitro, PDGF-AA, 47,48 PDGF-BB, 47 and PDGF-AB 47,49 were shown to be potent chemoattractants for human bMSC, with PDGF-BB generating the strongest response. 47 PDGF-AB also stimulated chemotaxis by ovine bMSC.…”
Section: Pdgf-aa Pdgf-ab Pdgf-bbmentioning
confidence: 99%
See 1 more Smart Citation
“…PDGF has two receptor dimers, a and b. PDGF-AA binds a/a receptors, PDGF-AB binds a/a and a/b receptors, and PDGF-BB binds a/a, a/b, and b/b receptors. 46 In vitro, PDGF-AA, 47,48 PDGF-BB, 47 and PDGF-AB 47,49 were shown to be potent chemoattractants for human bMSC, with PDGF-BB generating the strongest response. 47 PDGF-AB also stimulated chemotaxis by ovine bMSC.…”
Section: Pdgf-aa Pdgf-ab Pdgf-bbmentioning
confidence: 99%
“…by human bMSC, 48,70 suggesting that their role in fracture healing may include bMSC recruitment. BMP-2 and -7 delivery have been studied extensively in animal models, and it has been approved as a clinical treatment for fracture nonunions and large segmental defects.…”
Section: Bmp-2 Bmp-4 Bmp-7 Tgf-b1 Tgf-b3mentioning
confidence: 99%
“…Here, the development of scaffold materials which are able to enrich cells with regenerative potential in the affected area is a promising approach. Both processes, cell attraction and vascularisation, can be stimulated by chemoattractive factors (Richardson et al, 2001;Kanczler et al, 2008;Mishima and Lotz, 2008;Thieme et al, 2009). With the aim of utilising the natural binding properties of heparin for functionalisation of mineralised collagen matrices with such factors, we have developed two approaches for heparin-modification: integration during material synthesis ('in situ') or addition after scaffold-fabrication ('post') König et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Attracting factors include BMPs (Frenkel et al, 1996), hepatocyte growth factor (HGF) (Takebayashi et al, 1995), IGF-1 (Chang et al, 2003), TGF-ÎČ (Chang et al, 2003), PDGF (Fujita et al, 2004), FGF (Hidaka et al, 2006), fibronectin, fibrin and collagen type I (Maniwa et al, 2001). However, results remain contradictory for some of these factors, as testing of human chondrocytes revealed no effects for BMP-2, BMP-4, BMP-7, IGF and TGF-ÎČ in other studies (Mishima &, Lotz, 2008), being IGF-1, PDGF (Fiedler et al, 2004;Ozaki et al, 2007;Ponte et al, 2007) and VEGF the ones that induced higher response (Mishima & Lotz, 2008). Effects of GFs vary in vitro and in vivo, regarding animal species and specimens' age, among other aspects.…”
Section: Mesenchymal Stem Cells Therapymentioning
confidence: 97%
“…Besides, the lack of filling and the possible dead space between cylindrical grafts can limit the repair quality and integrity. Lane et al transplanted autologous osteochondral grafts into sheep knee joints and reported the lack of integration of the cartilage, which determined the persistence of gaps through the full thickness in all the specimens (Mishima et al, 2008). Fig.…”
Section: Autologous Osteochondral Transplantation: Mosaicplastymentioning
confidence: 99%